Gas Dynamical Capillary Flowmeters of Small and Micro Flowrates of Gases - Ivan Stasiuk (Energy Engineering and Control Systems)
The possibility of application of glass capillary tubes (CTs) as sensors of small and micro flowrates of gases was justified. The accuracy of a number of CTs flowrate equations was analyzed on the basis of experimental studies of CTs flowrate characteristics. It was shown that CTs can be applied as primary devices of small and micro flowrates of gases without individual calibration. The results of studies on the dynamic properties of gas dynamical capillary flowmeters of small and micro flowrates of gases constructed on the basis of glass CTs in the branches of a measuring bridge diagram are presented. The effects of various factors on the dynamic properties of the gas dynamical capillary flowrate transducers (GDCFTs) were analyzed. Recommendations on construction of the inter-capillary pneumatic measuring chambers (PMCs) of GDCFTs to provide the needed dynamic properties of the flowmeters are presented. The technique for defining the needed ratio of PMCs volumes in a GDCFT to provide the needed dynamic properties of the flowmeters on the stage of their design and construction is described.